2016
DOI: 10.17531/ein.2016.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gas network failure and failure prediction using the Monte Carlo simulation method

Abstract: Article citation info: IntroductionIn the report of the Committee of Union Gas in the World Congress in Nice in 1972, the issue connected with the failure intensity of the gas network was presented. Operation of Gas Supply System is inseparably linked with the occurrence of the fire and explosion risk. Failures, explosions and fires long-term statistics conducted by the gas services and organizational units of the State Fire Service indicate that despite the continuous increase of the safety level of gas suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…(a) On the basis of the values of the failure rate, it was found that the gas-pipeline network is characterized by a good technical state, which was confirmed by the authors' previous studies in other gas supply systems [21,38]. The failure rate for pipelines made of steel is λ steel = 0.075 km −1 ·a −1 , and the failure rate for pipelines made of plastics is λ p = 0.18 km −1 ·a −1 .…”
Section: Discussionsupporting
confidence: 74%
“…(a) On the basis of the values of the failure rate, it was found that the gas-pipeline network is characterized by a good technical state, which was confirmed by the authors' previous studies in other gas supply systems [21,38]. The failure rate for pipelines made of steel is λ steel = 0.075 km −1 ·a −1 , and the failure rate for pipelines made of plastics is λ p = 0.18 km −1 ·a −1 .…”
Section: Discussionsupporting
confidence: 74%
“…[14], freezing of ground around the water pipe e.g. [15], climatic or ground conditions eg. [16], [17], failures caused by earthworks e.g.…”
mentioning
confidence: 99%
“…x j is the first-stage decision made before the random variable is observed, ω s is the random variable with a probability level p s (i.e., the probability of realization of ω s , with p s > 0 and ∑ S s=1 p s = 1) [29], and y js is the second-stage adaptive decision, which depends on the realization of the random variable. function ( e j is cost coefficient of y js ).…”
Section: Methodsmentioning
confidence: 99%